Implementasi Teknik Rewarming terhadap Peningkatan Suhu Tubuh pada Pasien Hipotermi Pasca Operasi dengan Anestesi Spinal - Fitri Handayani; Danang Tri Yudono; Fauziah Hanum; Made Suandika (Yayasan Inspirasi El Burhani, 2026)
Introduction: Hypothermia is a common complication in postoperative patients, particularly following spinal anesthesia, which may cause discomfort, increase infection risk, delay wound healing, and prolong recovery time. Preliminary data at RSI Fatimah Cilacap showed that approximately 80% of patients undergoing spinal anesthesia experienced mild to moderate hypothermia, while current management remains largely pharmacological. Objective: The purpose of this service was to implement a rewarming technique using hot packs and aluminum foil blankets to improve body temperature in postoperative hypothermic patients following spinal anesthesia. Method: This public service was conducted on 30 postoperative patients who met hypothermia criteria (body temperature <36°C) in the recovery room of RSI Fatimah Cilacap. The methods included patient education, body temperature monitoring, application of hot packs to the inner arms for 15 minutes, and the use of aluminum foil blankets for 15–30 minutes. Result: The results demonstrated a significant increase in patients’ body temperature, with an average rise of 1.2°C after 15 minutes of combined intervention. There was also a reduction in shivering grade, with patients at grade 0 increasing from 57.7% to 93%. Most patients (83.3%) achieved recovery within 15 minutes, indicating the effectiveness of the rewarming method. Conclusion: The combination of hot packs and aluminum foil blankets is an effective non-pharmacological intervention to increase body temperature and reduce shivering in postoperative hypothermic patients following spinal anesthesia.